Psychometric properties of the spiritual intelligence scale on a sample of post-primary education students in the Omani environment - Alfarisi, Saja Said Khamis; Alkiyumi, Mohammed Talib Musallam (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to verify the psychometric properties of the spiritual intelligence scale in the Omani environment, where the King (2008) measure of spiritual intelligence was standardized, which was applied to a sample of 258 male and female students aged between 16-18 years of eleventh grade students. For post-primary education in the State of Suwaiq. The results of the study, which relied on the descriptive approach, indicated that the scale had psychometric properties consistent with the characteristics of a good scale. The scale's content validity was measured by content validity, internal consistency, factor validity, discriminatory validity and structural validity, which gave important, acceptable and statistically significant indicators. The reliability coefficient using the Alpha Cronbach equation for this scale, which amounted to 0.88, and the split-half method using the Spearman-Brown equation, which amounted to 0.89, so the current scale is valid for use and application in the Omani environment. The study recommends to take advantage of the current scale in the process of diagnosis, guidance and direction in the educational field.
Keywords: psychometric properties; post-primary education; validity; reliability; spiritual intelligence